PERAN PROGRAM MAGANG JEPANG BAGI PETANI MUDA DALAM MEREGENERASI PETANI INDONESIA - Ahmad Syariful Jamil; Resti Prastika Destiarni (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
Future problems in the Indonesian agricultural sektor are not only limited to the stagnation of agricultural commodity production, but also the regeneration of young Indonesian farmers. The agricultural sektor is experiencing an aging workforce, where most of the agricultural sektor workforce is dominated by elderly farmers. One of the government's efforts to overcome this problem is the issuance of the Japanese Apprenticeship Program for Young Farmers. Therefore, this study aims to analyze the role of the program in regenerating Indonesian farmers. As many as 50 program alumni who are members of the Japan Apprenticeship Alumni Association were used as respondents. Determination of respondents based on purposive sampling, with consideration of the distance. The qualitative descriptive analysis approach was used in order to answer the research objectives. The results showed that all of the respondents' alumni continued their business in agriculture after returning to Indonesia. In terms of operating income, there was an increase in operating income before and after alumni from Japan. In addition, there has been an increase in the number of employees employed by the respondent's alumni. This indicates an effort made by alumni in order to empower the surrounding community. Thus, the Japanese apprenticeship program has made a positive contribution to efforts to regenerate farmers in the agricultural sektor. In order to provide comprehensive input, further research is needed to quantitatively analyze the impact of the program on the regeneration rate of farmers.